2023
DOI: 10.1001/jamanetworkopen.2023.27415
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm Events and Suicide Deaths Among Autistic Individuals in Ontario, Canada

Abstract: ImportanceReasons for elevated suicide risks among autistic people are unclear, with insufficient population-based research on sex-specific patterns to inform tailored prevention and intervention.ObjectivesTo examine sex-stratified rates of self-harm events and suicide death among autistic individuals compared with nonautistic individuals, as well as the associated sociodemographic and clinical risk factors.Design, Setting, and ParticipantsThis population-based matched-cohort study using linked health administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…However, two large and more recent studies identified differences in suicide attempt risk with autistic females at greater risk than autistic males (Hirvikoski et al, 2020;Kõlves et al, 2021). Martini et al (2022) and Lai et al (2023) also both found higher risk for autistic females than males when examining self-harm codes. Hand et al (2020) found no differences between autistic males and females when looking at suicidal ideation.…”
Section: Understanding the Influence Of Sex On Autistic Suicide Riskmentioning
confidence: 97%
See 2 more Smart Citations
“…However, two large and more recent studies identified differences in suicide attempt risk with autistic females at greater risk than autistic males (Hirvikoski et al, 2020;Kõlves et al, 2021). Martini et al (2022) and Lai et al (2023) also both found higher risk for autistic females than males when examining self-harm codes. Hand et al (2020) found no differences between autistic males and females when looking at suicidal ideation.…”
Section: Understanding the Influence Of Sex On Autistic Suicide Riskmentioning
confidence: 97%
“…Suicide risk is a general phrase that is often used to refer to the risk of a wide range of suicidal behaviors. Existing evidence about autistic suicide risk includes studies using a variety of metrics including death by suicide (e.g., Hirvikoski et al, 2016;Kirby et al, 2019;Lai et al, 2023), suicide attempts (i.e., actions taken with the intent of dying; e.g., Hirvikoski et al, 2020;Kõlves et al, 2021), and suicidal thoughts or feelings (e.g., Cassidy et al, 2014). Not all suicide metrics have the same prevalence or associations, so it is imperative that the studied outcome is defined.…”
Section: Interpreting Studies On Suicide Risk In Autistic Communitiesmentioning
confidence: 99%
See 1 more Smart Citation